Socialization and Education on COVID-19 Prevention: Efforts to Raise Public Awareness - Mafaza, Akmalia Fitri; Sari, Mayang; Zuhri, Zainullah; Irsyadiah, Nur (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service program in Desa Sambiroto addresses the issue of raising awareness about COVID-19 prevention protocols. The initiative aimed to improve the community's understanding and compliance with health protocols, such as wearing masks, using hand sanitizers, and setting up handwashing stations. The ABCD (Asset-Based Community Development) approach was employed, leveraging local assets and community participation to create sustainable solutions. The strategy involved direct outreach to households, coordination with local leaders, and the use of educational media, including posters and videos. The results indicated a significant increase in adherence to health protocols, with enhanced usage of masks and improved hand hygiene practices. This program demonstrates the critical role of education and community engagement in mitigating the spread of COVID-19.